Reducing renal failure: how low do glucose levels need to go?. (January 2012) - Lo, Clement; Zoungas, Sophia
SUMMARY Diabetic kidney disease is the commonest cause of end-stage kidney disease worldwide. One strategy to prevent the development and progression of diabetic kidney disease is intensive blood glucose control. Randomized controlled trials such as the UKPDS and DCCT have demonstrated that a target HbA1c level of 7% improves renal outcomes. More recently, ACCORD, ADVANCE and VADT have explored the effects of targeting even lower HbA1c levels of 6.0–6.5%. These contemporary trials have universally reported improvements in albuminuria but no clear effects on preventing end-stage kidney disease. Thus, the additional and likely long-term renal benefits of intensive glucose lowering to achieve HbA1c levels ≤7% need to be balanced against the potential risks of intensive therapy such as severe hypoglycemia. An individualized approach is required with the understanding that the greatest renal benefits are likely to be achieved at a HbA1c level of ≤7%. Other risk factors for renal impairment should also be addressed.